Analysis of Water Distribution in Building A in Widyatama University Environment: Analisis Distribusi Air Gedung A di Lingkungan Universitas Widyatama - Suryaman, Nia Nuraeni; Komarudin, Udin; Martoni; Prasetia, Adhita; Santoso, Heru; Fahruddin, A'rasy (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2024)
The need for clean water increases every year, while the means to provide clean water require planning. The importance of water in the realm of education is comparable to that of household needs. Water on the 3rd and 4th floors of Building A often doesn't flow. The aim of this research is to identify the root cause of the insufficient water flow on the 3rd and 4th floors of Widyatama University Building A, and to devise a solution for the water flow distribution system. The research employs a variety of methods, including literature review, data collection, data analysis, results analysis, and interpretation. The conclusion is that the water drainage on the 3rd and 4th floors is 0.612 L/s and 0.510 L/s, which is below the standard (0.9–2 L/s). The drainage of water in the main pipe was uncertain based on its diameter. The solution to this problem is to install booster pumps on the 3rd and 4th floors. The next solution is to change the main pipe diameter to 1 1⁄4".